Harambee! 2.0: Community resources and resilience factors to leverage for improving HIV testing behaviors among African immigrant communities in Seattle, Washington - Shukri Ahmed Hassan; Najma Sheikh; Guiomar Basualdo; Nahom Daniel; Ahmed Ali; Rahel Schwartz; Beyene Tewelde Gebreselassie; Farah Mohamed; Mohamed Shidane; Sophia Benalfew; Bethel Tadesse; Hirut Amsalu Libneh; et al. (PLoS ONE, 2025)
Significant challenges promoting positive HIV testing behaviors among African immigrant communities in the U.S. persist, though existing community resources may be leveraged to improving these behaviors and increasing testing uptake. We conducted 30 key informant interviews and five focus group discussions (n = total 72 participants) among members of the Ethiopian, Somali, and Eritrean communities in Seattle, WA to identify these resources. Our findings highlight the following three main themes for responsive interventions: (1) capitalize on religious leaders and institutions as key facilitators; (2) leverage existing community resources, such as ethnic community centers, health boards, and healthcare professionals; and (3) utilize existing culturally-rich media for health promotion, centering on multi-linguality, -culturality, and -generationality. Our findings suggest that a wealth of community resources and resilience factors exist to leverage to improve HIV testing behaviors among African immigrant communities in the U.S.